Affiliation and disease risk: social networks mediate gut microbial transmission among rhesus macaques. (May 2019) - Balasubramaniam, Krishna N.; Beisner, Brianne A.; Hubbard, Josephine A.; Vandeleest, Jessica J.; Atwill, Edward R.; McCowan, Brenda
Abstract : In social animals, affiliative behaviours bring many benefits, but also costs such as disease risk. The ways in which affiliation may affect the risk of infectious agent transmission remain unclear. Moreover, studies linking variation in affiliative interactions to infectious agent incidence/diversity have speculated that disease transmission may have occurred, rather than revealing that transmission did occur. We address these gaps using the phylogenetics of commensal gut Escherichia coli to determine whether affiliative grooming and huddling social networks mediated microbial transmission among rhesus macaques. We collected behavioural and microbial data from adult macaques across a 12-week period that was split into two 6-week phases to better detect dyadic transmission. We reconstructed undirected social networks from affiliative interactions and reconstructed microbial transmission networks from the pairwise phylogenetic similarity of E. coli pulsotypes from macaques within and across adjacent sampling events. Macaque E. coli pulsotypes were more phylogenetically similar to each other than to environmental isolates, which established a premise for socially mediated transmission. Dyadic grooming and huddling frequencies strongly influenced the likelihood of E. coli transmission during the second data collection phase, but not the first. Macaques that were more central/well connected in both their grooming and huddling networks were also more central in the E. coli transmission networks. Our results confirmed that affiliative grooming and huddling behaviours mediate the transmission of gut microbes among rhesus macaques, particularly among females and high-ranking individuals. The detectability of socially mediated E. coli transmission maybe partially masked by environmental acquisition in males, or by high frequencies of interactions in captivity. Predicting the potential transmission pathways of gastrointestinal parasites and pathogens, our findings add to current knowledge of the coevolutionary relationships between affiliative behaviour and health and may be used to identify 'superspreader' individuals as potential targets for disease control strategies. Highlights: Affiliative behaviour brings health-related benefits, but also costs like disease risk. The links between affiliation and infectious agent transmission remain unclear. In rhesus macaques, social grooming and huddling mediated E. coli transmission. Macaques central in both social and transmission networks were 'superspreaders'. Our findings add to current knowledge of the coevolution of sociality and health.